Effects of laminarin on the structural properties and in vitro digestion of wheat starch and its application in noodles. (15th March 2023) - Wei, Zhixi; Ou, Yujia; Lan, Xiaoling; Tang, Junjie; Zheng, Baodong
Abstract: In this study, wheat starch (WS) was combined with different concentrations of laminarin (LM) to investigate changes in its microstructure, structure and digestibility. The application of LM to improve the cooking and textural properties of wheat noodles was also investigated. A low concentration of LM (2%, g/100g) reduced the crystallinity and order degree of WS, but a high concentration had the opposite effect. After LM addition, the leached amylose content and swelling power of WS were significantly reduced, indicating that LM coats the starch granule surface, inhibiting swelling and reducing amylose leaching. The addition of LM also significantly changed the microstructure of WS; WS granules aggregated in the presence of LM, forming a denser structure. In vitro digestion indicated that LM strongly inhibits the digestibility of WS, with 6% LM (g/100g) having the strongest inhibitory effect. Cooking and textural analysis of noodles showed that the addition of LM could improve the textural quality of noodles, by reducing cooking loss, increasing water absorption and hardness, and reducing adhesiveness. Highlights: Wheat starch(WS) was prepared with laminarin with heating treatment. Laminarin(LM) addition enhanced slowly-digestible and resistant starch in system. The relative crystallinity of WS was increased with the high concentration of LM. LM addition improved the textural and cooking properties of wheat noodle.